Impact of dental diseases on quality-sdjusted life expectancy in US adults: $hY. Matsuyama, G. Tsakos, S. Listl, J. Aida, and R.G. Watt - Matsuyama, Yusuke; Listl, Stefan (Journal of dental research, 2019)
Comparing the burden of dental conditions to other health outcomes provides useful insight for public policy. We aimed to estimate quality-adjusted life expecta...